A durable and sustainable superhydrophobic surface with intertwined cellulose/SiO2 blends for anti-icing and self-cleaning applications - Yu Wang; Qian Zhang; Pingping Li; Jin-Tian Huang (Materials & Design, 2022)
Poor wear resistance and the use of toxic chemicals restrict the marketization of most traditional superhydrophobic surfaces. The present work provides a method to prepare a durable and non-toxic superhydrophobic coating on the surface of a cotton fabric. Thermal polymerization of spray drying was used to obtain uniform structure of TEMPO-oxidized cellulose (TOC) with nano silica (SiO2), for achieving well-combined rough sphere-like micron particles with hierarchical dimensions, which were then immersed into isocyanate (IPDI) and polydimethylsiloxane (PDMS) respectively along with cotton fabric to construct a superhydrophobic coating on the fabric surface. The surface morphology, chemical structure, roughness and wettability of TOC-SiO2/PDMS surface were studied by adjusting the mass ratios of SiO2 to TOC. The optimal superhydrophobicity was obtained while the mass ratio of SiO2 to TOC was 1:1, displaying a water contact angle (CA) of 158.6°. The introduction of the intertwined TOC-SiO2 blends can construct a hierarchical micro-nano structure to enhance the hydrophobicity, simultaneously improve the mechanical durability of the superhydrophobic surface to prevent multiple peeling and friction damage, as well as outstanding chemical stability in a variety of harsh conditions.